Therapy of chagas disease in the Canton Aguarico, Ecuadorian Amazon - Amunárriz, Manuel (Revista Universidad de Guayaquil, 2011)
Determine the response of a seropositive population for Chagas disease an established therapy with nifurtimox. We selected 60 positive people out of 73 detected in the canton Aguarico in 2008 and 2009 (82.19%). It made them a therapy with nifurtimox 60 days in duration, at home and controlled with regular visits. Adherence was assessed individually in taking the treatment. Was used for the analysis of test results the same microELISA used in the tests performed to establish seroprevalence in Canton Aguarico. Se could assess the outcome of therapy established in 56 of the 60 seropositive (93.33%). Twenty-four gave “non-reactive” test before microELISA (42.85%). The analysis of adherence to the set of allowed cataloging treated in three groups: A: Full membership (23/56), B: irregularity in the taking of medication (12/56) C: abandonment of medication (21 / 56). Group A, with a success in the treatment of 100%. The results of the nifurtimox therapy are significant and encouraging to establish programs that address the issue of treatment of Chagas disease, both indeterminate and chronic, in our Ecuadorian Amazon region.